The integration of online advertising: the effects of source expertise and certainty level of the message on consumer involvement and persuasion in the context of user-generated advertising - Svede, Elina (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics